Culturable Plastisphere from the 75° N Subarctic Transect as a Potential Vector of Pathogens and Antibiotic-Resistant Bacteria - Gabriella Caruso; Maria Papale; Alessandro Ciro Rappazzo; Maurizio Azzaro (Journal of Marine Science and Engineering)
Plastic pollution is a global emerging concern, but in the Arctic Ocean, the role of the plastisphere as a potential carrier of pathogens and antibiotic-resistant bacteria is unknown yet. An initial assessment of the spread of these target bacteria through their colonization of plastic particles, attributed to the micro-sized fraction (less than 5 mm, named microplastics, MPs), was carried out across the 75° N transect (Greenland Sea). To fill the knowledge gaps regarding the bacterial community associated withmicroplastics (MPs)—belonging to the so-called “plastisphere”—and the potential risks related to their spread, our study focused on the abundance and taxonomic composition of the plastisphere, including potential pathogenic and antibiotic-resistant bacteria, using a culture-dependent approach. MPs particles were collected through a Manta net, and decimal dilutions were cultured on Marine agar plates to estimate the abundance of culturable heterotrophic bacteria. For the search of target pathogenic bacterial species (Escherichia coli, Enterococcus spp., Salmonella spp., potentially pathogenic Vibrio spp., and Staphylococcus aureus), small volumes were inoculated into selective culture media using aspread plate directly or after enrichment. Screening of the antibiotic susceptibility profiles of the bacterial isolates was performed to assess the presence of antibiotic-resistant bacteria. The culturable heterotrophic bacterial community was dominated by members of the phyla Gammaproteobacteria and Actinobacteria, with bacterial isolates assigned to the genera Psychrobacter, Pseudoalteromonas, Shewanella, and Arthrobacter. Selective enrichments resulted in the detection of target bacterial pathogens, mostly identified as potentially pathogenic Vibrios spp., in the examined samples. The antibiotic susceptibility profiles pointed out that multiple antibiotic-resistant bacteria were also isolated, suggesting the need to shed light on the potential risks to human and animal health deriving from the plastisphere in remote cold regions as well.